Could submarine groundwater discharge be a significant carbon source to the southern Baltic Sea? - Anna Maciejewska (Oceanologia, 2014)
Submarine Groundwater Discharge (SGD) is an important yet poorly recognised pathway of material transport to the marine environment. This work reports on the results of dissolved inorganic carbon (DIC) and dissolved organic carbon (DOC) concentrations and loads in the groundwater seeping into the southern Baltic Sea. Most of the research was carried out in the Bay of Puck (2009-2010), while in 2013 the study was extended to include several other groundwater seepage impacted areas situated along the Polish coastline. The annual average concentrations of DIC and DOC in the groundwater were equal to 64.5 ± 10.0 mg C L-1 and 5.8 ± 0.9 mg C L-1 respectively. The carbon specific flux into the Bay of Puck was estimated at 850 mg m-2 yr-1. The loads of carbon via SGD were scaled up for the Baltic Sea sub-basins and the entire Baltic Sea. The DIC and DOC fluxes via SGD to the Baltic Sea were estimated at 283.6 ± 66.7 kt yr-1 and 25.5 ± 4.2 kt yr-1. The SGD derived carbon load to the Baltic Sea is an important component of the carbon budget, which gives the sea a firmly heterotrophic status.